Pengembangan Media E-Commerce Sebagai Upaya Peningkatan Akses Pasar Pada Galeri UMKM wilayah Kabupaten Nagan Raya - Banta Diman (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The Handicraft Small and Medium Enterprises Gallery is a gallery facilitated to increase the marketing of handicraft products in the Nagan Raya district, so that it can encourage economic development for the community. One of the strategies that can be applied to increase the productivity of the Nagan Raya Regency Handicraft Small and Medium Enterprises Gallery is to apply digital-based promotional media so that it can expand market coverage and increase sales of products being marketed. The promotional media that will be developed in this research is a marketing promotion media based on E-Commerce. The development of e-commerce-based businesses is also inseparable from the development of the digital economy era which encourages all marketing sectors to utilize technology, so that Small and Medium Enterprises that are unable to optimize the use of technology will certainly find it difficult to develop and compete. The method for developing e-commerce-based marketing media is carried out by using the Rapid Application Development (RAD) method. The RAD method is a development method that can be carried out in a short time. The results of e-commerce development in this study were also carried out by implementing several stages as follows: planning stages, marketing media design stages, and implementation and evaluation stages. From the development results obtained, e-commerce development can increase market access that has a broad scope without having to be limited by space and time.